Effects from Periastron Advance of Eccentric Binary Stars - 李瑾 仲元红 潘宇 (Communications in theoretical physics, 2012)
In this paper,we discuss the coefficients of Gravitational waveform due to eccentric binaries periastron advance with evolved eccentricity.For the basic harmonic modes（n ≤ 5）,the frequency split and corresponding relative strengths in the spectrum are figured out.Taking the well known binary systems PSRB 1913＋16 and PSRB 1534＋12 as examples,we study the dominant harmonic and its frequency split caused by periastron advance in the spectra,and give an estimation of detectability for PSRB 1913＋16 and PSRB 1534＋12,which are the promising targets for space observatories of gravitational wave.